Assessing Groundwater Connection/Disconnection to Waterholes Along the Balonne River and in the Barwon–Darling River System in Queensland and New South Wales, Australia, for Waterhole Persistence - Harald Hofmann; Jonathan Marshall (Hydrology)
Waterholes in semi-arid environment are sections of rivers that fill during high river flows or floods and keep water once flow ceases. They are essential water sources for rive ecosystems. Some waterholes remain even during prolonged droughts. The resilience of ecosystems in these environments depends on the persistence of the waterholes. While most semi-arid, ephemeral river systems are disconnected from regional groundwater and losing in most parts there may be some sections that can be connected to localised groundwater or parafluvial areas. To assess the persistence of waterholes the groundwater contribution to the water balance needs to be addressed. This study assesses groundwater connectivity to waterholes in a part of the Murray-Darling Basin, one of the largest watersheds in the world, using environmental tracers radon and stable isotopes. Approximately 100 samples were collected from 27 waterholes along the Narran, Calgoa, Barwon and Darling rivers, as well as 8 groundwater bore samples. The assessment of groundwater connectivity or the lack of is necessary from water balance modelling and estimation of persistence of these waterholes. As expected, the results indicate consistently low radon concentrations in the waterholes and very small deviation in stable isotopes <semantics>δ18</semantics>O and <semantics>δ2</semantics>H. In general, most of these waterholes are losing water to groundwater, indicated by low salinity (EC values) and low radon concentrations. While radon concentrations are small in most cases and indicative of little groundwater contributions, some variability can be assigned to bank return and parafluvial flow. It indicates that these contributions may have implications for waterhole persistence in ephemeral streams. The study demonstrates that in some cases local bank return flow or parafluvial flow may contribute to waterhole persistence.